BIAYA ADMINISTRASI PEMBIAYAAN DI BAITUL MAAL WAT TAMWIL (BMT) DALAM PERSPEKTIF EKONOMI ISLAM - BAYU SUDRAJAT; MASNGUDI . (J-EBI (Jurnal Ekonomi Bisnis Islam), 2023)
AbstractBMT provides financing services to the community with the implementation and its products refer to Al-Qur'an and Hadith interpreted in the fatwa of the national sharia council of clerics indonesia. In realizing the financing, BMT also implements the administrative cost of financing as a pre-requisite to be paid by the member of the financing if the financing is realized. The absence of definite technical rules in determining the size of the administrative costs of financing makes the BMT in determining the administrative costs tend to adopt the ways undertaken by conventional financial institutions where in determining administrative costs based on a percentage of the size of the nominal financing. This shows the possibility of the BMT looking for its own advantages behind the administration of financing, because the greater the cost it will be the greater the administrative costs to be paid.Keywords, BMT; Financing; Financing Administration Cost